THE SŌMA AND THE PSYCHĒ IN THE GOSPEL OF MATTHEW AND IN PLATO’S TIMAEUS - Loh, Yip (PEOPLE: International Journal of Social Sciences, 2016)
Both Christianity and Plato claim that the psychē is immortal, that there is life after death. However, Plato’s theory of the psychē has been misinterpreted by some Christian scholars and theologians, who rail against Greek philosophy for distorting Christianity’s doctrine of the psychē, and who hold further that Plato’s theory of the psychē is a dualism. This thesis will prove that Plato does not assert the sōma-psychē bipartite, and try to solve the Christian debate between the sōma-psychē bipartite and sōma, psychē and pneuma tripartite. The importance of Plato’s Timaeus in the ancient world - particularly in the Academy - is the same as that of the Bible in the modern one. This paper will focus on Plato’s Timaeus with the help of his Phaedo and Gorgias to discuss his theory of the birth of the psychē and sōma and the relationship between them. So the main purpose of this article is to inquire into the Gospel of Matthew, thus I hope to show the similarities and the discriminations between the relative thought of Christianity and of Plato. Furthermore, I would like to illustrate that Plato is not a dualist, contrary to the assertions of some Christian scholars.